Educational tourism in the context of global challenges - N. A. Ofitserova (Вестник университета)
The article is devoted to educational tourism which currently acts as one of the promising technologies of modern education, demonstrating a steady demand for it despite the aggravated geopolitical and socio-economic situations, and that explains the relevance of this issue. An important goal of educational tourism is formation of a comprehensively developed personality capable of vigorous activity in a multiethnic and multicultural environment. On the basis of characteristic features of educational tourism described in this article, a definition is formulated in which the integrative nature of the studied type of tourism is identified. In addition, the main directions of educational tours are given that allow to get the most complete picture of this social phenomenon alongside with the advantages of educational trips for both the host country and the student. The paper considers the Russian export of educational services, which makes it possible to increase the stability of the local economy. Some relevant initiatives contributing to the development of educational tourism in Russia have also been studied. The arguments justifying the need for its immediate development are presented as well as the tasks that require priority solutions for this. It is concluded that tourism and education are the key drivers for the development of the modern economy.